2011
DOI: 10.1001/jama.2011.1851
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorders, Health, and Safety in Police Officers

Abstract: Among a group of North American police officers, sleep disorders were common and were significantly associated with increased risk of self-reported adverse health, performance, and safety outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
320
4
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(340 citation statements)
references
References 50 publications
8
320
4
8
Order By: Relevance
“…For example, the sample of rapidly rotating shift workers examined by Flo E et al [8] included many females (90% of the subjects), and they reported that a woman has 0.57 times the rate of SWD than a man. Rajaratnam SM et al [18] estimated that SWD, defined as excessive sleepiness and insomnia, was present in 14.5% of police officers who worked night shifts. However, their estimate increased markedly, to 53.9%, when the ICSD-2 criteria (excessive sleepiness or insomnia) were applied, and 82% of their subjects were male.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the sample of rapidly rotating shift workers examined by Flo E et al [8] included many females (90% of the subjects), and they reported that a woman has 0.57 times the rate of SWD than a man. Rajaratnam SM et al [18] estimated that SWD, defined as excessive sleepiness and insomnia, was present in 14.5% of police officers who worked night shifts. However, their estimate increased markedly, to 53.9%, when the ICSD-2 criteria (excessive sleepiness or insomnia) were applied, and 82% of their subjects were male.…”
Section: Discussionmentioning
confidence: 99%
“…Los trastornos del sueño constituyen un problema que, además de afectar la salud, la productividad, la calidad de vida y la seguridad del individuo, tienen consecuencias importantes en la salud pública (1). Algunas revisiones sistemáticas señalan que tanto el sueño corto (<7 horas) como el sueño excesivo (>9 horas) se asocian a un mayor riesgo de mortalidad por todas las causas (2,3).…”
unclassified
“…On the other hand, although sleep disorders are common, they can remain undiagnosed and if they are not taken care of they can adversely affect the health and safety of the police agents and also put the public at risk [11]. Found in a group of North American policemen that sleep disorders were common and were signi icantly associated with their health status, their performance and their own safety [12].…”
Section: Discussionmentioning
confidence: 99%